Spicebush Swallowtail, Papilio troilus Linnaeus (Insecta: Lepidoptera: Papilionidae) - Donald W. Hall; Jerry F. Butler (EDIS)
The spicebush swallowtail butterfly is a large, dark swallowtail. It is one of our most beautiful and interesting swallowtails. All developmental stages are great examples of adaptive coloration. This document is EENY-168, one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.